The association between selected mid-trimester amniotic fluid candidate proteins and spontaneous preterm delivery. (16th February 2020) - Hallingström, Maria; Cobo, Teresa; Kacerovsky, Marian; Skogstrand, Kristin; Hougaard, David M.; Holst, Rose-Marie; Tsiartas, Panagiotis; Bullarbo, Maria; Carlsson, Ylva; Nilsson, Staffan; Jacobsson, Bo
Abstract: Objective: The aim of this study was to explore inflammatory response and identify early potential biomarkers in mid-trimester amniotic fluid associated with subsequent spontaneous preterm delivery (PTD). Methods: A cohort study was performed at Sahlgrenska University Hospital/Östra, Gothenburg, Sweden, between 2008 and 2010. Amniotic fluid was collected from consecutive women undergoing mid-trimester transabdominal genetic amniocentesis at 14–19 gestational weeks. Clinical data and delivery outcome variables were obtained from medical records. The analysis included 19 women with spontaneous PTD and 118 women who delivered at term. A panel of 26 candidate proteins was analyzed using Luminex xMAP technology. Candidate protein concentrations were analyzed with ANCOVA and adjusted for plate effects. Results: The median gestational age at delivery was 35 + 3 weeks in women with spontaneous PTD and 40 + 0 weeks in women who delivered at term. Nominally significantly lower amniotic fluid levels of adiponectin (PTD: median 130, 695 pg/mL (IQR 71, 852–199, 414) vs term: median 185, 329 pg/mL (IQR (135, 815–290, 532)), granulocyte-macrophage colony stimulating factor (PTD: median 137 pg/mL (IQR 74–156) vs term: median 176 pg/mL (IQR 111–262)), and macrophage migration inhibitory factor (PTD: median 3025 pg/mL (IQR 1885–3891) vs term: median 3400 pg/mL (IQR 2181–5231)) were observed in the spontaneous PTD group, compared with the term delivery group, after adjusting for plate effects. No significant differences remained after Bonferroni correction for multiple comparisons. Conclusions: Our results are important in the process of determining the etiology behind spontaneous PTD but due to the non-significance after Bonferroni correction, the results should be interpreted with caution. Further analyses of larger sample size will be required to determine whether these results are cogent and to examine whether microbial invasion of the amniotic cavity or intra-amniotic inflammation occurs in asymptomatic women in the mid-trimester with subsequent spontaneous PTD.